2013
DOI: 10.1007/s00277-013-1873-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of a prospective randomized trial evaluating G-CSF priming in intensive induction chemotherapy followed by autologous stem cell transplantation in elderly patients with acute myeloid leukemia

Abstract: Few studies have evaluated granulocyte colony-stimulating factor (G-CSF) priming in elderly patients with intensively treated acute myeloid leukemia (AML), and no data are available for genetically defined AML subgroups. We provide long-term results (median follow-up 7.6 years) of a randomized trial in which 183 patients (median age 67 years) received G-CSF prior to (G-CSF priming) or after two cycles of induction chemotherapy. CR rates with G-CSF priming and G-CSF post-chemotherapy were comparable (57 vs. 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The survival after the first relapse is also significantly increased for group 1 (p = 0.03). These results are in line with reports from literature stating that autonomous leukemic cell growth has a negative impact on patient prognosis 4 , 5 and also with the finding that in some trials patient subgroups with unfavorable risk do not respond to cytokine priming before chemotherapy 11 , 12 .
Figure 5 Patient data compatible only with model of cytokine independent AML correlates with poor overall survival.
…”
Section: Resultssupporting
confidence: 92%
“…The survival after the first relapse is also significantly increased for group 1 (p = 0.03). These results are in line with reports from literature stating that autonomous leukemic cell growth has a negative impact on patient prognosis 4 , 5 and also with the finding that in some trials patient subgroups with unfavorable risk do not respond to cytokine priming before chemotherapy 11 , 12 .
Figure 5 Patient data compatible only with model of cytokine independent AML correlates with poor overall survival.
…”
Section: Resultssupporting
confidence: 92%
“…Based on reports of improvement in DFS and OS in adult patients with ‘standard risk’ AML , we used G‐CSF concurrent with chemotherapy. The use of G‐CSF in elderly patients with AML has been scarcely assessed, and several studies have shown a trend to better relapse‐free survival without improvement in OS .…”
Section: Discussionmentioning
confidence: 99%
“…This was a long-term (median follow-up 7.6 years) randomized trial in which 183 patients (median age 67 years) received G-CSF prior to (G-CSF priming) or after two cycles of induction CT. They found little or no improvement and concluded that G-CSF priming should be restricted to normal karyotype AML and used only in post-remission therapy [102].…”
Section: Toxicology Of Drugs Used In Elderlymentioning
confidence: 98%
“…Several studies have been carried out to determine the optimum time and type of growth factor administration [99][100][101]. However, a recent study by Bug et al [102] evaluated granulocyte colony-stimulating factor (G-CSF) priming in elderly patients with intensively treated AML. This was a long-term (median follow-up 7.6 years) randomized trial in which 183 patients (median age 67 years) received G-CSF prior to (G-CSF priming) or after two cycles of induction CT.…”
Section: Toxicology Of Drugs Used In Elderlymentioning
confidence: 99%